PENGARUH DIMENSI FRAUD TRIANGLE TERHADAP KECURANGAN AKADEMIK MAHASISWA AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS NUSA CENDANA - Maria Theresia Dhao; Sarinah Joyce M. Rafael; Linda Lomi Ga (Globalwriting Academica Consulting & Publishing, 2022)
This study aims to determine the effect of the fraud triangle (pressure, opportunity and rationalization) on student academic cheating behavior in students of the accounting study program, Faculty of Economics and Business, Nusa Cendana University. This research is a quantitative research method with data collection in the form of questionnaires distributed via google form, which is measured using a Likert scale ranging from 5-1. The population of this study were students of class 2017, 2018 and 2019 which amounted to 662 students. The sampling method used in this study was purposive sampling method, so that a sample of 61 respondents was obtained, which was obtained from the results of distributing questionnaires through google form. The data analysis method used is multiple linear regression using SPSS version 25. The results of this study indicate that the variables of pressure, opportunity and rationalization have no significant effect on academic cheating students of the Faculty of Economics and Business, Nusa Cendana University. The reason why it has no effect, this lies in the number of samples in this study which is too small, which is only 61 respondents. Another reason is that students of the accounting study program at the Faculty of Economics and Business at Nuca Cendana University, especially students from the 2017 2018 and 2019 batches, realize that there is no need for them to commit academic fraud for any reason.